Regional Portal FVG: Effective Interoperability through DSpace-CRIS and Open Standards - Piščanc, Jordan; Trampus, Romano; Balbi, Luisa; Mennielli, Michele; Mornati, Susanna; Pascarelli, Luigi Andrea; Bollini, Andrea (Elsevier BV, 2025)
THUMBNAIL